PEMANFAATAN STORYTELLING SIRAH NABAWI BERBASIS MEDIA CANVA UNTUK MENINGKATKAN PENDIDIKAN KARAKTER ISLAMI ANAK DI TK ALFIKH ORCHARD - Rihan Alfitra Daudy; Zailani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This qualitative study investigates the implementation of Canva-based Sirah Nabawi storytelling in early childhood education. Data were collected through observations, interviews, and documentation. Results indicate that while teachers faced challenges due to limited digital literacy and inadequate facilities (e.g., lack of projectors), children exhibited high engagement and curiosity. Furthermore, the storytelling effectively fostered prosocial behaviors, such as empathy toward animals. The study concludes that Canva-based storytelling enhances motivation and Islamic character values, though its success depends on improving teachers' digital competencies and school infrastructure.